Advanced computational model for Peltier effect based refrigerators. (25th February 2016) - Martinez, A.; Astrain, D.; Rodriguez, A.; Aranguren, P.
Highlights: Outperforms any other simulation model for thermoelectric refrigerators. Transient state with temperature-dependent Seebeck, Peltier, Joule and Thomson. Construction and testing of a prototype for model validation and verification. ±10% of maximum deviation from experimental values of the main outputs. Assessment of temperature-independent properties. Abstract: Computational models emerge as essential tools in the challenge of developing competitive thermoelectric refrigerators for the domestic sector. This paper presents a computational model for thermoelectric refrigerators that simulates the entire system under transient state, including the thermoelectric modules, heat exchangers, insulated compartments, and hot and cold reservoirs. Also, temperature-dependent Peltier, Seebeck, Thomson and Joule effects are implemented. A prototype of a thermoelectric refrigerator has been built and tested to conduct the verification and validation of the computational model. The most important outputs are predicted with deviations lower than ±10%. The effect on the outputs of temperature-independent properties has been assessed. Results indicate that deviations are up to twice as high as those obtained for temperature-dependent properties, so these simplifications are invalid in the simulation of thermoelectric refrigerators under real operation.